Geographic and energy-aware routing in Wireless Sensor Networks. (19th March 2009) - Yang, Dengfeng; Li, Xueping; Sawhney, Rapinder; Wang, Xiaorui
Energy efficiency is crucial for large scale sensor networks due to the intrinsic resource constraints of the wireless sensors and the infeasibility to change depleted batteries that may reside in hostile environments. This paper proposes an energy efficient routing algorithm based on a two-layer Wireless Sensor Network (WSN) architecture to maximise the lifetime. The proposed scheme takes advantage of the geographic deployment knowledge to build routing protocols. Linear Programming (LP) formulations are developed to maximise the lifetime of WSNs. A Hybrid Energy-efficient Routing Scheme (HERS) is proposed to incorporate both max-min residual energy and min-max communication energy consumption information. Simulation results show that the proposed routing algorithms can prolong the lifetime of a WSN compared to the existing algorithms.